PEMBERDAYAAN MASYARAKAT MELALUI AKTIVITAS BERKESENIAN DI DESA GEBLOG KECAMATAN KALORAN KABUPATEN TEMANGGUNG - suharji suharji (Institut Seni Indonesia Surakarta, 2020)
This article aims to foster public love for traditional arts through scientific disciplines.Directing and fostering the competence of students to observe, analyze, and discover the potentialand challenges that exist in society. The approach used is social change. Methods include crossscientificapproaches, action reviews, and innovative creative actions to get to know each otherbetween the coach and the local villagers, estimate the time span, and adjust to the surroundingcommunity environment.Outreach Results, offer programs (mediation), and program implementation.Implementation of activities contributes to the maturity of students in addressing existing problemsand can understand how to live in society. Students grow in awareness to form an independentpersonality and are responsible for their tasks and functions as well as forming a leadership spirit.Keywords. Empowerment, Art, Society, Geblog